A Return-to-Work Intervention for Prematurely Retired Depression or Anxiety Disorder Patients - Behrens-Wittenberg, Eva; Wedegaertner, Felix (Frontiers in Psychiatry, 2021)
Depression and anxiety disorders are the most common cause for premature retirement of people of middle age. These people are expelled from the workforce. The following social disintegration can have an additional detrimental effect on subjects’ psychological well-being which further reduces the chance to re-enter the workforce. Depression and anxiety in general need not be regarded as irreversible causes of disability. Therefore, long-term disability should be avoidable in many cases. This two-arm prospective controlled study tests a novel approach for those who have become economically inactive due to their illness with the goal to improve psychological well-being and return to work. 41 subjects were followed-up on over a period of 12 months and compared to 41 control cases. ANOVA for repeated measures showed that experimental subjects’ psychological well-being and work ability was much better after the intervention than in the control group. These findings show that an individually tailored return-to-work intervention can be a useful therapeutic tool even after retirement.